A Class of High Performance Electrocatalysts for Oxygen Reduction Reaction of Fuel Cells, using Iodine Doped Graphene. (2018) - Marinoiu, Adriana; Varlam, Mihai; Carcadea, Elena; Raceanu, Mircea; Soare, Amalia; Stefanescu, Ioan
Abstract: Low cost, sustainable and high performance electrocatalysts for oxygen reduction reaction (ORR) which can replace/reduce rare metals base catalysts are highly desirable for the effective commercial development of fuel cells. In this paper, we report a class of low cost electrocatalyst with highly performance for ORR, obtained by graphene doping with iodine precursor. It can be one of the most promising alternatives to Pt-based catalysts to date. Iodine doped graphene based materials were prepared by nucleophilic substitution and characterized by different techniques, including Scanning Electron Microscopy SEM, wavelength dispersive X-ray fluorescence WDXRF, that revealed the structure and morphology. The iodinated graphene was sprayed on gas diffusion layer (GDL) and tested in a single cell PEMFC. The electrochemical performances of fuel cell with/without iodinated graphene under typical experimental conditions were evaluated, namely current-voltage polarization and cyclic voltammetry curves, electrochemical impedance spectroscopy (EIS).